Tirguamme: An Ethiopian Methodological Contribution for Post-Socialist Knowledge Traditions in Africa - Woldeyes, Yirga Gelaw (Sense Publishers, 2017)
The Geez term tirguaamme translates as the art of giving meaning to reality or text. It is an act of interpreting the world, a process of creating new meaning out of existing meanings (past, present, foreign, local) and practices. Tirguaamme as social practice takes place in popular wisdom as expressed in the Wax and Gold tradition, allegorical puzzles, the traditional debate on truth claims and other forms of inquiring, debating and reflecting. In the traditional education system, students learn tirguaamme especially in metsehaf bet (house of books) and qine bet (house of critical poetry), as a method of reaching the hidden meaning of a text by interpreting it based on diverse life contexts and the creation of complex and multiple meanings using poetry. As a traditional practice of interpretation through creative incorporation and critical reflection, tirguaamme enabled (and, in traditional schools, still continues to enable) Ethiopians to produce knowledge from diverse sources and use it in the traditional education system. Creative incorporation is the process of interpreting knowledge from foreign sources, while critical meditation is the practice of reflecting on social issues, as evidenced in the meditation of Zara Yacob. This chapter argues that traditions such as tirguaamme can become dynamic and relevant sources of knowledge for postsocialist education in Africa.